Measuring spirituality above religiosity: efforts to suppress the procrastination of teachers of Christian education through the internalization of love - Ariawan, Sandy; Kristyana, Kristyana; Wahyuni, Sri (KURIOS (Jurnal Teologi dan Pendidikan Agama Kristen), 2021)
The purpose of this study is to identify the internalization of love as an effort to suppress the procrastination of teachers of Christian education. Christian education in the New Testament is a pivoted education on the Great Teacher of Jesus Christ. It is a Divine and human effort that has existed for a long time and continues to undergo changes in which it contains philosophical and theological content whose function produces life changes that draw one closer to establishing a relationship with God. This research was conducted using quantitative approaches with descriptive methods of correlation. The population distribution in this study was teachers of Christian education in North Sumatera, represented by 42 respondents as a sample (N=42). The sampling technique used was random sampling and be analyzed with simple regression analysis. The correlation that occurs between the two variables is 0.614. It appears that the effect of the effort to internalize love on Suppressing Procrastination is 37,7%, while the other 62,3% is influenced by other factors. The process of internalization which is an embodiment of spirituality has a positive influence, which can overcome the inability to encourage yourself to make a duty to be done. It is suggested subsequent studies regarding the theme in the larger populations and finding another form of internalization to confirm and develop the results of this research.